Are Antibiotics Needed in Septorhinoplasty? An Evidence-Based Approach - Mantelakis, Angelos; Argiris, Konstantinos; Joshi, Anil; D'Souza, Alwyn Ray (Facial Plastic Surgery, 2022)
The use of prophylactic antibiotics in the context of septorhinoplasty (SRP) is a frequently debated topic among plastic surgeons. Most surgeons routinely use antibiotics to prevent the dreaded physical and psychological morbidity of postoperative infections, although this practice is controversial. With antimicrobial resistance becoming a global threat, however, optimizing antibiotic prescribing is essential. The current evidence would suggest that the rate of postoperative infection is low and routine antibiotic use is unnecessary in SRP surgery. Rates range from 0.5 to 2% in simple SRP surgery, majority of which are minor nasal infections which respond to oral antibiotics and do not require hospital admission. In cases of complex SRP, defined as revision cases or where grafts or implants have been utilized, infection rates can be much higher with an incidence of 7 to 11%, and as such utilization of antibiotics is reasonable. When considering the regime to be utilized, a single preoperative dose of intravenous antibiotics has the same efficacy in reducing the incident of postoperative infection as a postoperative 7-day course of oral antibiotics. In the authors' practice, all patients receive a single intravenous dose of antibiotics on induction, and in the case of utilization of a graft from a nonnasal site, this is complimented with an oral course of postoperative antibiotics. With this approach, infections rates are at the lowest range of available published literature.
Keywords: antibiotics; septorhinoplasty; antibiotic resistance; rhinoplasty